2019
DOI: 10.19113/sdufenbed.494396
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Machine Learning and Deep Learning for Time Series Forecasting: A Case Study of Choosing the Best Prediction Model for Turkey Electricity Production

Abstract: Over the last decades, Turkey pays special attention to electricity production to afford its needs. Researchers applied different methodologies including statisticalbased and artificial intelligence-based to correctly predict the future amount of electricity production, consumption, and demand. However,limited researchers focused on Turkey's electricity production prediction problem as a time series analysis. For this reason, we tackle this problem by considering it as a time series analysis in this study. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Hamdoun et al comprehensively analyzed and evaluated various traditional, machine learning, and DL methods for time series forecasting problems related to various energy sources [17]. Ramazan employed different approaches, including traditional machine learning algorithms such as Support Vector Regression (SVR) and Multilayer Perceptrons (MLP), and DL algorithm Long Short-Term Memory (LSTM), to create a better model for handling Turkey's monthly electricity production dataset [18]. The research results demonstrated that LSTM outperformed SVR and MLP methods in commonly used statistical error evaluation indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hamdoun et al comprehensively analyzed and evaluated various traditional, machine learning, and DL methods for time series forecasting problems related to various energy sources [17]. Ramazan employed different approaches, including traditional machine learning algorithms such as Support Vector Regression (SVR) and Multilayer Perceptrons (MLP), and DL algorithm Long Short-Term Memory (LSTM), to create a better model for handling Turkey's monthly electricity production dataset [18]. The research results demonstrated that LSTM outperformed SVR and MLP methods in commonly used statistical error evaluation indicators.…”
Section: Literature Reviewmentioning
confidence: 99%